2020
DOI: 10.17776/csj.762184
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic properties of Vitamin C: A theoretical work

Abstract: Vitamin C is an important human micronutrient. It has many vital biological functions in human health. In this research paper, the molecule of vitamin C was optimized and energy band gaps were determined using DFT and HF methods. In computational quantum theory, Density Functional Theory (DFT) and Hartree-Fock (HF) currently play a significant role in physical chemistry spatially. We chose a 6-311+G basis set on the DFT and HF methods to assess our vitamin C molecule. The FT-IR spectra of vitamin C are reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 54 publications
1
15
0
Order By: Relevance
“…GaussView5.0, a molecular imaging tool, was used to map the three-dimensional form of the molecular compounds in the gas phase and the base case [17,18]. The GaussView 5.0 packet program was used to establish the starting geometries of the molecules, and the Gaussian09W software was used to perform the calculations [19,20]. Because the electron density is taken into consideration in the DFT approach, it can produce the needed data for a more accurate measurement of the electronic characteristics of compound structures [21,22].…”
Section: Calculation Methodsmentioning
confidence: 99%
“…GaussView5.0, a molecular imaging tool, was used to map the three-dimensional form of the molecular compounds in the gas phase and the base case [17,18]. The GaussView 5.0 packet program was used to establish the starting geometries of the molecules, and the Gaussian09W software was used to perform the calculations [19,20]. Because the electron density is taken into consideration in the DFT approach, it can produce the needed data for a more accurate measurement of the electronic characteristics of compound structures [21,22].…”
Section: Calculation Methodsmentioning
confidence: 99%
“…The energy difference between HOMO and LUMO defines the molecular electrical transport properties. The energy gap of HOMO-LUMO can be used to determine molecules' global chemical reactivity descriptors such as hardness, chemical potential, softness, electronegativity and electrophilicity index [21,[34][35][36][37][38]. Table 4 and Figure 6, demonstrate the energy band gap of HOMO-LUMO for PPN.…”
Section: Descriptors Of Global Reactivitymentioning
confidence: 99%
“…Gökalp, 2016 reported the thermodynamical properties of PPN by using DFT and HF at the level of B3LYP/6-31+g(d,p) [6,7] Zazeri et al, 2019 investigated experimental and computational modeling of rat serum albumin and its interaction with PPN [8] Besides, Choudhary et al, 2020 reported of molecular docking of PPN [9] Alves et al, 2020 explained the experimental and theoretical spectra of PPN [10] The polarity of the solvent and the mode of solute to solvent interaction can effect on geometry, dipole moment, polarizability, hyper-polarizability, and other molecular properties (s) [11][12][13] via variable interactions with molecular orbitals of the highest occupied (HOMO) and lowest unoccupied (LUMO) [11,13,14] and, thus, could affect the molecule's reactivity and stability. DFT calculations would be used to provide information on molecular characteristics and interactions, which essentially contributes to understanding properties of molecular [15][16][17][18][19][20][21][22] As part of our continuing study [23][24][25][26] but for PPN molecule, the current research was conducted to study the medium impact of PPN on solvation free energy, dipole moment, polarizability, first-order hyperpolarizability and chemical reactivity, which could be beneficial in more understanding the stability of PPN in various solvent systems.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the analysis and anticipation of a molecule's reactive behavior can be effectively carried out using the EMP. The space surrounding the nuclei and electrons in a molecule is considered as the generate charge distributions [33,34]. Various colors denote different electrostatic potential values, where red indicates the most negative value and blue represents the most positive value.…”
Section: Molecular Electrostatic Potentialmentioning
confidence: 99%